Numerical Simulation of Treatment Capacity and Operating Limits of Alkali/Surfactant/Polymer (ASP) Flooding Produced Water Treatment Process in Oilfields - Jiawei Zhu; Mingxin Wang; Keyu Jing; Jiajun Hong; Fanxi Bu; Zhihua Wang (Energies, 2025)
As an enhanced oil recovery (EOR) technique, alkali/surfactant/polymer (ASP) flooding effectively mitigates production decline in mature oilfields through chemical flooding mechanisms. The breakthrough of ASP chemical agents poses challenges to the green and efficient separation of oilfield produced water. In this paper, sedimentation separation of produced water was simulated using the Eulerian method and the RNG k–ε model. In addition, the filtration process was simulated using a discrete phase model (DPM) and a porous media model. The distribution characteristics of oil/suspended solids obtained through simulation, along with the water quality parameters at each treatment node, were systematically extracted, and the influence of operating conditions on treatment capacity was analyzed. Simulations reveal that elevated treatment loads and produced water polymer concentrations synergistically impair ASP flooding produced water treatment efficiency. Fluctuations of operating conditions generate oil/suspended solids content in output water ranges spanning 13–78 mg/L and 19–92 mg/L, respectively. The interpolation method is adopted to determine the critical water quality parameters of each treatment node, ensuring that the treated produced water meets the treatment standards. The operating limits of the ASP flooding produced water treatment process are established.